Third-Space Endoscopy: Recent Updates - Nabi, Zaheer; Reddy, D Nageshwar (Journal of Digestive Endoscopy, 2021)
Third space or submucosal space is a potential space which on expansion allows the endoscopist to execute a multitude of therapeutic procedures for various gastrointestinal diseases like achalasia, subepithelial tumors, Zenker’s diverticulum, and refractory gastroparesis. Third space was first utilized for performing endoscopic myotomy in cases with achalasia cardia about a decade ago. Since then, the field of submucosal endoscopy has witnessed an exponential growth. The present review focuses on recent advances in the field of third-space endoscopy. With regard to per-oral endoscopic myotomy (POEM) in achalasia cardia, several recent studies have evaluated the long-term outcomes of POEM, compared endoscopic myotomy with pneumatic dilatation (PD) and surgical myotomy, and evaluated the outcomes of short- versus long-esophageal myotomy. In addition, the utility of multiple dose antibiotic prophylaxis to prevent infections after POEM has been questioned. Overall, the results from these studies indicate that POEM is a durable treatment modality, equally effective to Heller’s myotomy and superior to PD. With regard to gastric-POEM (G-POEM), recent studies suggest only modest efficacy in cases with refractory gastroparesis. Therefore, quality studies are required to identify predictors of response to optimize the outcomes of G-POEM in these cases. Another third-space endoscopy procedure that has gained popularity is endoscopic division of septum in cases with esophageal diverticula including Zenker’s POEM and epiphrenic diverticula POEM (Z-POEM and D-POEM, respectively). The technique of diverticulotomy using the principles of submucosal endoscopy appears safe and effective in short term. Data on term outcomes are awaited and comparative trials with flexible endoscopic myotomy required. Per-rectal endoscopic myotomy (PREM) is the most recent addition to third space endoscopy procedures for the management of short-segment Hirschsprung’s disease. Limited data suggest that PREM may be a promising alternative surgery in these cases. However, quality studies with long-term follow-up are required to validate the outcomes of PREM.
Keywords: submucosal endoscopy; achalasia; gastroparesis; Zenker’s diverticulum